ANALYSIS OF MORALITY AND TAXPAYER'S TAXPOSITION BEHAVIOR TO THE COMPLIANCE WITH INDIVIDUAL TAXATION 2017-2019 - Supardi,; Sinaga, Obsatar; Haizam Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
The definition of tax according to Law Number 16 of 2009 concerning General Provisions and Tax Procedures in Article 1 paragraph 1 is a mandatory contribution to the state owed by individuals or entities that are forcing based on the Law, with no direct and direct compensation. used for the needs of the country for the interests and prosperity of the people. The tax compliance ratio always increases and decreases inefficiently, this is due to the lack of discipline of taxpayers and the active role in tax obligations. This study aims to determine whether the level of Tax Knowledge and Tax Examination significantly influence the compliance of individual taxpayers in the city of Bandung. This study uses Primary data obtained from distributing questionnaire data to the Parties concerning the criteria of this Research. The data analysis method used is classic assumption test. The statistical method used in this research is multiple linear regression analysis. The researcher use partial significant test and simultaneous significance test to test the hypothesis. The results revealed that tax knowledge partially had a positive effect on the level of corporate tax compliance, and tax audits had no negative effect on the level of personal tax payer compliance. Meanwhile, based on simultaneous research, tax knowledge, and tax audits have a significant positive effect on the level of corporate tax-payer compliance.